2021
DOI: 10.1038/s41598-020-78624-4
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of extracellular matrix modeling with molecular prognostic markers revealed by transcriptome sequencing and validations in Oral Tongue squamous cell carcinoma

Abstract: Oral Tongue Squamous Cell Carcinoma (OTSCC), a distinct sub-group of head and neck cancers, is characteristically aggressive in nature with a higher incidence of recurrence and metastasis. Recent advances in therapeutics have not improved patient survival. The phenomenon of occult node metastasis, even among the purportedly good prognosis group of early-stage and node-negative tongue tumors, leads to a high incidence of locoregional failure in OTSCC which needs to be addressed. In the current study, transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Thangaraj et al found a strong connection between grade and Ki 67 in a retrospective examination of the Ki-67 index and its prognosis. 18 Significance in Over 800 primary breast cancer cases. Ki-67 expression levels were shown to be substantially linked with histological grade in all patients in research by Liang et al (p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Thangaraj et al found a strong connection between grade and Ki 67 in a retrospective examination of the Ki-67 index and its prognosis. 18 Significance in Over 800 primary breast cancer cases. Ki-67 expression levels were shown to be substantially linked with histological grade in all patients in research by Liang et al (p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are several reports on the diagnostic and predictive value of Lng2 immunohistochemistry in OSCCs. Among others, a correlation has been shown between a diffuse expression of Lng2 in disseminating and infiltrating tumor cells, with higher grades of malignancy, poor prognosis, and a higher risk for nodal metastasis observed in patients with tongue cancer [66][67][68][69]. Furthermore, shorter life expectancy in OSCCs with an increased number of Lng2-positive tumor cells [70], an elevated risk for transformation in Lng2-positive pre-neoplastic mucosal lesions [71,72], as well as a higher risk for nodal metastasis [20,73,74] could be evidenced.…”
Section: Laminin γ2 Chain Reorganization In the Oscc Invasive Front: ...mentioning
confidence: 99%
“…The results suggest that these desmosomal components may work as tumor suppressors in HNC. However, the functional study of gain or loss and immunohistochemistry identification of desmosomal components have revealed contradictory roles for some desmosome members, including DSG2 [65,[73][74][75], DSG3 [26,65,66,76], PKP1 [27,77,78], and PG [70,79,83] in HNC, suggesting that the role of the desmosomal components in HNC may be affected by some other signal transduction molecules or/and modifications related to the tumor microenvironment. Additionally, like other tumors, subcellular location, PTM, inactivation by proteolytic cleavage, and the biogenesis of regulating extracellular vesicles (EVs) may also affect the role of desmosomes in HNC.…”
Section: The Expression and Significance Of Desmosomal Components In Hncmentioning
confidence: 99%